When Meaning Becomes Controversial: Critical Questions for Assessing Semantic Arguments - Pruś, Jakub; Macagno, Fabrizio (Informal Logic)

(untitled) (Informal Logic, 2024)
This paper aims to develop the criteria for assessing semantic arguments. However, while this notion constituted the core of ancient dialectics and is addressed in several approaches to argument analysis, the criteria for evaluating such arguments are insufficient. This paper intends to address this problem by combining the insights of classical and contemporary logic and testing them against some controversies involving controversial definitions or classifications. Through detailed case studies of the argumentative uses involving the (re)definitions of racism, war, peace, and feminism, we formulated and tested eight evaluation criteria that may be expressed as critical questions.